The Role of Cultural Factors in Consumer Behavior on Purchasing Decisions for Herborist Products - Irensi Seppa, Yusi; Darmayanti, Dyan Paramitha (Pinisi Business Administration Review, 2024)
Cultural factors greatly influence consumer behavior. Cultural factors influence consumer behavior, which can be seen from lifestyles, habits, and traditions in the demand for different goods and services. The purpose of this study is to find out more about how cultural factors influence consumer behavior when they choose to buy Herborist products. Descriptive qualitative research is the type of research used because it can help researchers by explaining the facts that exist in the field. Data collection techniques included observation, interviews, and documentation. Data analysis is the first stage of the data reduction process, which focuses on selecting, simplifying, abstracting, and transforming rough data from field notes. The second stage is data presentation, where information is organized into statements that allow conclusions to be drawn, and the third stage is conclusion drawing based on data reduction and presentation. The results showed that cultural factors have the greatest and most significant impact on how consumers make purchasing decisions. Culture, subculture, and social class are some of the ways the role of cultural factors is demonstrated.